(untitled) (Research, Society and Development, 2021)
The purpose of this study was to evaluate the linear dimensional stability of four extended-pour irreversible hydrocolloids (EPIHs). Material and Methods: Five samples per material (Cavex ColorChange, Cavex Orthotrace, Jeltrate Plus, and Orthoprint) were prepared following the manufacturers’ instructions. The samples were prepared using a cylindrical matrix coupled with a nylon-polyamide ring. Two parallel, 25-mm equidistant lines were made on its surface following ANSI/American Dental Association (ADA) Specification 18 for plaster reproducibility and compatibility and Specification 19 for linear dimensional change. The samples were stored in an environment with a relative humidity of 70% (± 3) and temperature of 28°C (± 2). Photo images were obtained using a digital camera to record images for 120 hours, with a standardized distance of 80cm between the lens and the specimen. Adobe Photoshop CS3 software was used for the measurement of the recorded images. The measurements refer to the equivalent distance between the two parallel lines printed on the samples. Data were analyzed using one-way analysis of variance (ANOVA) and Tukey’s test for multiple comparisons between the means of the groups. Results: There was no statistically significant difference (p > 0.05) when EPIHs were compared at the same time of evaluation. Orthoprint, Cavex Orthotrace, and Cavex Colorchange presented with least dimensional stability up to 24 hours (p > 0.05) of storage, followed by Jeltrate Plus (48 hours). Conclusions: Storage of EPIHs for more than 24 hours for Cavex ColorChange and 48 hours for others EPIHs studied produces significant dimensional changes in the impressions stored at a humidity of 70% (± 3) and temperature of 28°C (± 2). Extended storage times produce large dimensional changes.